Pulse waves : How vascular hemodynamics affects blood pressure - Salvi, Paolo (Springer Milan, 2012)
How is blood pressure generated?  How can blood pressure values be interpreted? Is systolic blood pressure of greater importance than diastolic? These are some of the commonest questions a physician facing the problem of arterial hypertension must answer in everyday clinical practice. The aim of this book is to present the complex basic principles of vascular hemodynamics and its physiopathology in a direct and effective way, stressing the importance of the mechanical properties of large arteries in the origin of blood pressure. With the help of  several images and an easy language, the reader is led to discover the elements defining blood pressure, getting used to the concepts of arterial stiffness, pulse wave velocity, central blood pressure, reflected waves, pulse pressure amplification.